Accelerometer Based Control of Robotic Arm - Yogita sawant (IAES International Journal of Robotics and Automation (IJRA), 2016)
Abstract— Robots are very smart and interactive machines that can be programmed and used in many areas such as industry, manufacturing, production lines, household or health, etc. These robots can perform hard, dangerous, and accurate work to facilitate our life and to increase the production. Humans are trying to minimize the time required to do the similar kind of jobs. The task in which picking & placing of an object is to be done, can be carried out with the help of robots. These robots can minimize the human efforts. The robotic arms can be also used in the industries to assemble the small parts, in chemical industries to pick and place small types of object such as tablets. Artificial robotic arms thus can be used to control gestures. In this paper an  idea of controlling robotic arm is implemented using an accelerometer which is placed on the human hand, capturing its behavior (gestures and postures) which are then transmitted at some distance and the robotic arm assembly connected wirelessly moves accordingly.